Memahami Hadis-hadis Keutamaan Menghafal al-Qur’an dan Kaitannya dengan Program Hafiz Indonesia di RCTI (Aplikasi Hermeneutika Nasr Hamid Abu Zaid) - Ulummudin Ulummudin (AL QUDS : Jurnal Studi Alquran dan Hadis, 2020)
This paper aims to understand hadiths related to the benefit of memorizing the Qur’an in the contemporary era. The review is needed because now memorizing the Qur’an has been a trend and even exploited for the sake of commercial interest such as Hafiz Indonesia program in RCTI. The method which is used to explain the meanings of hadiths is Nasr Hamid Abu Zaid’s hermeneutic. The hermeneutic is trying to peel three levels of intended meaning. They are dalalat (meaning), maghza (significance), and maskut anhu (unspoken things). Based on the application of the hermeneutic, the result is that the meaning of the hadith is a form of motivation which was delivered by the prophet, so that the companions were enthusiastic for memorizing the Qur’an. The purpose is that the Qur’an had to be maintained for the next generations. The manner of keeping the Qur’an, according to that time tradition was by memorizing it. Meanwhile, the significance is practicing the teachings of the Qur’an in daily life. The Qur’an is not enough to only exist in their memories, but also it must be applied in their behavior. To get virtue and honor in the world and after life, individual piety (memorizing the Qur’an) must be parallel with social piety (interaction with the others). The last, its maskut anhu is a prohibition of memorizing the Qur’an for popularity and economic interest